Evolutionary Relationships of the Fish Prochilodus reticulatus and Prochilodus magdalenae (Characiformes: Prochilodontidae) (2018)
A phylogenetic study was carried out between the species Prochilodus reticulatus (Valenciennes, 1850) and P. magdalenae (Steindachner, 1879) of great socioeconomic value in the country. Initially, the species were collected for DNA extraction and subsequent characterization by RAPD-PCR to establish their phylogenetic relationships using the Jaccard coefficient and the UPGMA method. The phylogenetic analysis of P. reticulatus and P. magdalenae showed a close genetic relationship, which suggests that the differences found between them may not be considered significant.